Diel variation of CH4 and CO2 dynamics in two contrasting temperate lakes. Issue 3 (2nd July 2020) - Martinez-Cruz, Karla; Sepulveda-Jauregui, Armando; Greene, Samuel; Fuchs, Andrea; Rodriguez, Maricela; Pansch, Nina; Gonsiorczyk, Thomas; Casper, Peter
ABSTRACT: The concurrent short-term fluctuations of methane (CH4 ) and carbon dioxide (CO2 ) concentrations and emissions in lakes are not well studied. Quantifying the differences in daytime versus nighttime dynamics may provide information about the controls over greenhouse gas production and may have relevance to lake carbon budgets. In this study, the diel variation of CH4 and CO2 emissions and concentration patterns were determined along the water column of 2 temperate lakes with different trophic states during July 2015. The results showed that the shallow eutrophic lake had significantly higher CH4 and CO2 releases than the deep oligo-mesotrophic lake. No significant diel fluctuations were observed in atmospheric CH4 emissions from either lake or in CO2 emission from the oligo-mesotrophic lake, but significantly higher CO2 emission from the eutrophic lake occurred during the daytime compared to nighttime. Based on a diffusion–reaction model, it was possible to estimate the diel variation of the sources and sinks of dissolved CH4 throughout the water column, suggesting lateral transport is a potential source of CH4 in oxygenated water layers in the oligo-mesotrophic lake. Sources and sinks throughout the water column should be considered in future studies for a better understanding of CH4 dynamics within the lakes.